2019
DOI: 10.1103/physrevfluids.4.113602
|View full text |Cite
|
Sign up to set email alerts
|

Predicting droplet velocity in a Hele-Shaw cell

Abstract: We study the motion of low viscous non-wetting droplet in a Hele-Shaw cell, while it is pushed by an external phase of imposed flow rate, at low capillary numbers. In this regime, the droplet's mobility, defined as the ratio between the droplet velocity and the external phase mean velocity, evolves non linearly with the capillary number, a signature of the different dissipation mechanisms at play. Experiments are performed with surfactant free air bubbles in fluorinated oil, and with surfactant laden fluorinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 34 publications
4
11
0
Order By: Relevance
“…This domain C is far enough from the meniscus for the Laplace pressure to be negligible, but close enough from it so that the boundary condition difference on both interfaces is not screened. Such behaviour has already been observed and quantified for a meniscus in contact with a solid wall (Cantat 2011; Reichert, Cantat & Jullien 2019), and was conjectured in Petit (2014) for a free meniscus.…”
Section: Flow Properties In the Meniscus And Aroundsupporting
confidence: 54%
See 1 more Smart Citation
“…This domain C is far enough from the meniscus for the Laplace pressure to be negligible, but close enough from it so that the boundary condition difference on both interfaces is not screened. Such behaviour has already been observed and quantified for a meniscus in contact with a solid wall (Cantat 2011; Reichert, Cantat & Jullien 2019), and was conjectured in Petit (2014) for a free meniscus.…”
Section: Flow Properties In the Meniscus And Aroundsupporting
confidence: 54%
“…It is, however, usually observed that the velocity may vanish in such cases, this effect being known as the stagnant cap limit (Cuenot, Magnaudet & Spennato 1997; Cantat 2011; Reichert et al. 2019). In this limit, and in steady state, the whole flux advected on interface 2 must diffuse to interface 1, which imposes (as depicted in figure 15).…”
Section: Constitutive Relation For the Meniscusmentioning
confidence: 99%
“…This domain C is far enough from the meniscus for the Laplace pressure to be negligible, but close enough from it so that the boundary condition difference on both interfaces is not screened. Such behavior has already been observed and quantified for a meniscus in contact with a solid wall [32,33], and was conjectured in [34] for a free meniscus.…”
Section: B Meniscus Frustration -Domain Definitionssupporting
confidence: 57%
“…In compression, the surface excess Γ 2 (s m ) is larger than its equilibrium value and can not vanish. It is however usually observed that the velocity may vanish in such cases, this effect being known as the stagnant cap limit [32,33,40]. In this limit, and in steady state, the whole flux Φ 2 = u ∞ Γ ∞ advected on interface 2 must diffuse to interface 1, which imposes Γ ∞ u ∞ ∼ j ∼ −D δΓ 1 /(h ∞ h Γ ) (as depicted in Fig.…”
Section: Vanishing Flux At the Meniscusmentioning
confidence: 99%
“…The effective boundary condition used by Meiburg (1989) was improved by Burgess & Foster (1990), both to capture correctly the Bretherton pressure drop at the rear interface of a moving bubble, and to analyse inner regions where the liquid flow is approximately tangent to the bubble interface and the Park & Homsy (1984) model breaks down. Reichert, Cantat & Jullien (2019) included the Bretherton pressure drop in their model for an isolated circular bubble in a Hele-Shaw cell with a uniform background flow. Reyssat (2014) also included the Bretherton drag force in his model for a bubble in a Hele-Shaw cell whose walls are slightly inclined to form a thin wedge, and observed that the bubble migrates out of the wedge to reduce its surface area.…”
Section: Introductionmentioning
confidence: 99%